STUDYING THE MECHANISMS OF FOOT DEFORMATIONS AND THEIR IMPACT ON POSTURAL STABILITY: THE ROLE OF PHYSICAL THERAPY - Davybida, Nataliya; Korin, Petro; Novakova, Lyubov; Dovgan, Olena; Bezpalova, Nataliya; Nazaruk, Viktor (European Science, 2025)
111